2021
DOI: 10.1177/17562872211043341
|View full text |Cite
|
Sign up to set email alerts
|

The effect of medical and urologic disorders on the survival of patients with metastatic castration resistant prostate cancer treated with abiraterone or enzalutamide

Abstract: Introduction: Androgenic deprivation therapies have been linked to the development of metabolic syndrome (MS) and cardiovascular diseases, which may lead to a poorer survival in patients with metastatic Castration-Resistant Prostate Cancer (mCRPC). We aimed to analyze whether some cardiovascular or neurological disorders, together with other medical and urological complications, may have an effect on survival outcomes, at baseline and during treatment from patients treated with androgen pathway inhibitors (API… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…One study ( Benoist et al, 2018 ) strongly recommended to replace carbamazepine (DS = −5) during AA treatment. In addition, among the other drugs with negative DS, insulin (−3) and spironolactone (−1) have also been shown to impair the efficacy of AA treatment ( Serrano Domingo et al, 2021 ; Vicente-Valor et al, 2021 ). The positive effect present in our study of frequently used drugs with positive DS, like vitamin D (5) and pantoprazole (5), which is a proton pump inhibitor (PPI), should be emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…One study ( Benoist et al, 2018 ) strongly recommended to replace carbamazepine (DS = −5) during AA treatment. In addition, among the other drugs with negative DS, insulin (−3) and spironolactone (−1) have also been shown to impair the efficacy of AA treatment ( Serrano Domingo et al, 2021 ; Vicente-Valor et al, 2021 ). The positive effect present in our study of frequently used drugs with positive DS, like vitamin D (5) and pantoprazole (5), which is a proton pump inhibitor (PPI), should be emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Androgen deprivation therapy (ADT) is central to treating locally advanced and metastatic disease [7] by blocking the production of testosterone or curtailing its function to stop prostate cancer growth. Abiraterone acetate (AA), an androgen biosynthesis inhibitor, and enzalutamide (ENZ), an androgen receptor signalling inhibitor, are standard hormonal therapies that are mainstay additions to ADT.…”
Section: Introductionmentioning
confidence: 99%
“…Real-world studies showing the association between cardiovascular events related to hormonal treatments and preexisting metabolic, cardiovascular, or neurological conditions are limited [7,10,[15][16][17]. Furthermore, because differential adverse effects of AA and ENZ and their interactions with patient comorbidities have not been fully elucidated, there is little guidance on how to choose these drugs based on pre-existing conditions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, adverse drug effects (ADEs) are common with NHTs and may vary with patient and drug characteristics [ 8 ]. Limited real-world studies have shown associations between NHT toxicities and pre-existing metabolic, cardiovascular, or neurological conditions [ 12 , 13 ]. For instance, AA has been shown to significantly increase cardiomyopathy while ENZ increases hypertension [ 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%